The Impact Study of Abrasion Preventing Program in Dumai Coastal - Santosa, Fajar Julian; Fomandes, Zyqro Milid; Dewi, Titis Puspita; Wiraandika, Gatra; Agustiawan, Agustiawan (ENVIBILITY: Journal of Environmental and Sustainability Studies, 2025)
The coastal area of ​​Dumai City has experienced severe abrasion problems due to strong waves and tidal currents. In response to the increasing degradation of the coastline due to abrasion, various abrasion prevention programs have been implemented, one of which is through the construction of coastal protection structures in the form of Lancang Kuning wave breakers and mangrove rehabilitation on the coast. This study aims to evaluate the overall impact of abrasion prevention efforts that have been carried out on coastline stability, ecological sustainability, and the livelihoods of the surrounding community. This study uses a mixed-methods approach, which includes observation, field surveys, and in-depth stakeholder interviews. Mangrove rehabilitation efforts have shown positive ecological effects, while physical structures such as the aerodynamic Lancang Kuning wave breakers have helped reduce wave strength directly. In addition, mangrove replanting can withstand sand sedimentation, thereby reducing the impact of abrasion. The presence of mangroves planted on the coast is also a home for animals such as the scad, which are starting to reappear. However, this study also highlights challenges such as uneven implementation, maintenance problems, and sediment transfer to adjacent areas. In addition, further research is also needed on modeling shoreline changes before and after development. These findings suggest that more integrated and adaptive coastal management strategies are critical for long-term effectiveness.